Endothelial dysfunction in patients with type 2 diabetes post acute coronary syndrome. (July 2013) - Lumsden, Natalie G; Andrews, Karen L; Bobadilla, Maria; Moore, Xiao L; Sampson, Amanda K; Shaw, James A; Mizrahi, Jacques; Kaye, David M; Dart, Anthony M; Chin-Dusting, Jaye PF
This single visit study examined whether endothelial function, in addition to cardiovascular (CV) risk factors and plasma microparticle content, was normalised in 15 patients with type 2 diabetes + acute coronary syndrome (ACS) (6 weeks–6 months post cardiac event) undergoing standard clinical care compared to 16 sex- and age-matched healthy controls. Results: While total and low-density lipoprotein (LDL) cholesterol levels were well controlled in the patients with type 2 diabetes + ACS, residual CV risk profiles such as increased body mass index (BMI), systolic blood pressure, glucose levels and triglycerides and lower high-density lipoprotein (HDL) levels were still apparent. Endothelium-dependent responses to acetylcholine (ACh) were significantly lower in type 2 diabetes + ACS patients compared to controls. Correspondingly, the reactive hyperaemic index (RHI) was lower in the patient cohort. Endothelial microparticle (EMP) levels (CD31 +, CD41 − ) were 40% lower in the patient cohort. Simultaneous analysis of platelet microparticle (PMP) levels (CD41 + ) showed no difference between cohorts. Conclusions: Patients with type 2 diabetes suffering from recent ACS exhibit residual CV risk factors despite being on standard clinical care. In addition, these patients continue to present with endothelial dysfunction despite having lower levels of EMPs.